A migrasome-related lncRNA signature predicts prognosis and immune response in hepatocellular carcinoma: Implications for biomarker discovery and therapeutic targeting - Qin, Haotian; Qi, Tiantian; Liu, Min; Sheng, Weibei; Qian, Junyu; Weng, Jian; Yang, Qi; Yang, Jun (Frontiers in Pharmacology, 2025)
BackgroundHepatocellular carcinoma (HCC) remains a leading cause of cancer-related death, with limited response rates to immunotherapy. Identifying novel biomarkers to predict prognosis and guide treatment is urgently needed.MethodsUsing TCGA-LIHC data, we identified migrasome-related long non-coding RNAs (MRlncRNAs) associated with HCC prognosis and constructed a two-lncRNA signature (LINC00839 and MIR4435-2HG) through LASSO-Cox regression. The model was validated in an independent cohort (n = 100). Multi-omics analyses were conducted to explore correlations with immune infiltration, immune checkpoints, TMB, MSI, and therapeutic sensitivity. Clinical sample validation and functional assays were performed to verify biological relevance. We knocked down MIR4435-2HG in HCC cells to assess its impact on proliferation, migration, EMT phenotype, and PD-L1 expression.ResultsThe MRlncRNA signature effectively stratified HCC patients by prognosis and immunotherapy responsiveness. High-risk patients exhibited elevated immunosuppressive cell infiltration and immune checkpoint expression. Functional validation revealed that MIR4435-2HG promotes malignant behaviors and immune evasion by regulating EMT and PD-L1. Single-cell analysis showed its enrichment in cancer-associated fibroblasts, suggesting a role in tumor-stroma crosstalk and immune suppression.ConclusionMRlncRNAs, particularly MIR4435-2HG, contribute to HCC progression and an immunosuppressive tumor microenvironment. This study establishes a robust prognostic model and identifies potential targets for precision immunotherapy in HCC.